ANALISIS TINGKAT LITERASI KEUANGAN MAHASISWA (Studi Pada Mahasiswa S1 Universitas Sarjanawiyata Tamansiswa) - Silfeni Rahima Putri; Mujino Mujino; Risal Rinofa (Journal Competency of Business, 2018)
This study aims to determine the level of financial literacy in S1 Sarjanawiyata Tamansiswa University students using the scientific method (scientific method) that is to build one or more hypotheses based on a structure or theoretical framework which then tests the hypothesis empirically. The scientific method in this study uses a qualitative approach that is a research approach that works with numbers, the data in the form of numbers (scores or values, ranks and frequencies) are then analyzed using statistics to answer research questions or hypotheses that are specific in nature and make predictions that a certain variable affects a variable the other. The objects in this study are S1 Students at Sarjanawiyata Tamansiswa Faculty of Economics (Accounting and Management), and Non-Economic Faculties, among others: Family Welfare Empowerment (PKK), Indonesian Language and Literature Education (PBSI), English Language Education (PBI), Education Physics, Mathematics Education, Mechanical Engineering Education (PTM), Agribusiness, Agrotechnology, Elementary School Teacher Education (PGSD), Science Education, Fine Arts, Industrial Engineering, Civil Engineering, and Psychology. This study also aims to determine whether there is a relationship between age, gender, GPA, study program, year of entry, residence status, parental education and parental income to the level of financial literacy of Sarjanawiyata University Tamansiswa students. This study used a sample of 263 students including the Faculty Economics as many as 100 people and Non-Economics Faculty as many as 163 people. In the results of the analysis of the level of student financial literacy there are results that are 7 (0.2%) High category students, 209 (79%) Medium category students, 44 (1.8%) Low category students, and 3 (0.1 %) The category of students is very low, besides age, GPA, study program, year of entry, and parents' income have an influence on student financial literacy, while gender and parent's education have no influence on student financial literacy.